Teacher Collaboration and School Effectiveness in Ireland - Liam Murphy (CV Edujavare Publishing, 2025)
Teacher collaboration has emerged as a critical determinant of school effectiveness, particularly within the context of Ireland's evolving educational landscape. This study examines the relationship between teacher collaboration and school effectiveness in Irish primary and post-primary schools, drawing upon empirical evidence from professional learning communities, collaborative inquiry models, and national policy frameworks. The Irish education system has embedded collaborative learning as a stated principle within the Primary Curriculum and the post-primary Key Skills framework, reflecting a national commitment to participatory and cooperative pedagogies. However, the scale of implementation remains variable across schools, with persistent challenges related to time constraints, systemic fragmentation, and the assessment of collaborative competencies. Drawing on qualitative case studies from Dublin City University and comparative analyses with European frameworks, this paper identifies key mechanisms through which teacher collaboration enhances instructional quality, collective teacher efficacy, and student outcomes. Findings indicate that structured collaborative inquiry characterised by critical dialogue, public sharing of practice, and external facilitation yields measurable improvements in teacher beliefs, self-efficacy, and classroom practice. The study concludes that sustainable teacher collaboration requires intentional school leadership, dedicated time allocation, and alignment with career-long professional learning policies, including Ireland's Droichead induction process and Oide's continuing professional development offerings. These insights contribute to the broader discourse on school improvement and offer actionable recommendations for policymakers and school leaders seeking to cultivate collaborative cultures that drive educational excellence.